PENGARUH MODEL PEMBELAJARAN SNOWBALL THROWING TERHADAP MINAT BELAJAR SISWA KELAS IV DALAM PELAJARAN AKIDAH AKHLAK DI MI DAARUL AITAM PALEMBANG - Tri Juliyanti; Nuraeli; Amir Hamzah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of the implementation of the Snowball Throwing learning model on students’ learning interest in the Akidah Akhlak subject for fourth grade students at MI Daarul Aitam Palembang. The research method used was a quantitative method with an experimental approach. This study employed a pretest and posttest design involving two groups, namely the experimental class and the control class. Data collection techniques were carried out through learning interest questionnaires, observation, and documentation. Data analysis was conducted using statistical tests with the assistance of SPSS 31 software. The results of the study showed that the implementation of the Snowball Throwing learning model had a positive effect on students’ learning interest. This can be seen from the increase in the average score of the control class, which was 70.35, and the experimental class, which was 74.48, indicating differences between the control and experimental classes. Students’ learning interest increased after being given treatment compared to before the treatment. This learning model was able to improve students’ enjoyment, motivation, interest, and involvement in the learning process. Thus, it can be concluded that the Snowball Throwing learning model has a significant effect on improving students’ learning interest in the Akidah Akhlak subject for fourth grade students at MI Daarul Aitam Palembang.